Béla Mező interviewed by Alex Hood and Annette Hood in the Alex Hood folklore collection. - Mező, Béla, 1919-; Hood, Alex, 1935-; Hood, Annette, 1948- (2013)
Folkloric recording.
Recorded on 3 June 2013 in Elizabeth Bay, New South Wales.
Digital master available
Timed summary (5 pages)
Keywords: Mező, Béla, -- 1919- -- Interviews; Hungarians -- Australia -- Interviews; Physicians -- Australia -- Interviews; Psychiatrists -- Australia -- Interviews; Doctors; Psychiatrists